(untitled) (La U Investiga, 2017)
Being a Cantonal interest the proper waste management, the present study had the purpose of evaluating the treatment of the same in the different services of basic and specialized clinical laboratory of private character, through a descriptive investigation, that according to Morán seeks to specify properties, characteristics important profiles of people, groups subjected to analysis. (1) With a methodology of Inductive character, and documental analysis, allowed to arrive at the discovery of the scientific truth, through the generalization of the observed behavior. (2) It was sought to know the appreciation and knowledge of the problem both of the degree of understanding of laws on pollution, equipment, forms of treatment of different types of waste, documentation required and training of staff, using the anonymous survey as a tool and interviews with entities Involved in environmental management. With results of interest such as: 31,58% They know the sanctions in the country that indicate penalties for contamination of the environment by infectious material contagious and others. 59,65% They consider in total to make an appropriate waste management. 64.91% Consider having trained and trained personnel responsible for the management and treatment of waste 42.11% They have a manual that indicates how to do the management of wastes 24.56% Of the laboratories have autoclaves to use both clean material and waste management. 70.7% Do not disinfect waste dumps in laboratories. No treatment is given to 97% of urine, 98% of feces and 70.1% of processed blood.